Zgodovinski viri o Romih v Sloveniji - Klopčič, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
HISTORICAL SOURCES ON ROMA IN SLOVENIA. In the current discussion on the status of Roma in Slovenia, the significance of historic circumstances is often neglected, although these have contributed to the shaping of certain stereotypes, thus having caused and preserved the mutual distrust between the majority population and Roma. The authorities' approach to the problem of Romain the past shows a distinctly authoritarian and paternalistic features, as they demanded accurate supply of data on the migrations and settling of Roma in different municipalities. The purpose of these lists were either persecutions, expulsions or forceful settling of Roma at certain territories. These measures meant obstacles in mutual contacts between Roma nad non-Roma, isolation within Roma community and growing distrust towards any measures of the authorities. Consequently, distrust was also transmitted to those members of Roma community who had accepted the values and lifestyle of the majority nation. The article discusses some elements of approach towards integration of Roma community from the past periods, reflected in historical sources and original documents, from more than a century ago.
Keywords: Slovenia; Slovenija; Romi; zgodovinski pregledi; etnične skupine